Flower and foliage-infecting pathogens of marijuana (Cannabis sativa L.) plants. Issue 4 (2nd October 2018) - Punja, Zamir K.
Abstract: Flower buds of Cannabis sativa develop as inflorescences (buds) which are harvested and dried prior to sale. The extent to which fungal plant pathogens can colonize the buds prior to harvest has not been previously studied. Flower buds were sampled at various pre-harvest and harvest time periods during 2015–2017 at locations in British Columbia and Alberta to determine the range of fungi present. Isolated fungi were inoculated onto developing buds to determine the extent of tissue colonization. A pre- and post-harvest internal rot was associated with Botrytis cinerea, causing botrytis bud rot. In addition, two species of Penicillium – P. olsonii and P. copticola – were recovered from pre-harvest flower buds, as well as dried buds, and shown to cause penicillium bud rot. Scanning electron microscopy studies revealed colonization and sporulation on bracts and stigmas of the flower buds by P. olsonii . Several Fusarium species, which were identified using ITS rDNA sequences as F. solani, F. oxysporum and F. equiseti, were isolated from pre-harvest flower buds. These fungi colonized the flower buds following artificial inoculation and caused visible rot symptoms. The most severe symptoms were caused by F. solani, followed by F. oxysporum and, to a much lesser extent, F. equiseti . Powdery mildew infection of the foliage and flower buds was caused by Golovinomyces ( Erysiphe ) cichoracearum . The pathogen was detected on young vegetatively propagated cuttings and sporulation was abundant on older plants and on flower buds. The various fungi recovered from cannabis flower buds may be present as contaminants from aerially dispersed spores and have the potential to cause various types of pre- and post-harvest bud rot under conducive environmental conditions. Powdery mildew may be spread through aerially disseminated spores and infected propagation materials. Management of these pathogens will require monitoring of the growth environment for spore levels and implementation of sanitization methods to reduce inoculum sources.